Passive drag reduction for green design - Asrar, Waqar; Aymeric , Goulet; Tristan, Mazou Berges (2012)
Experimental results of passive drag reduction are presented for the case of a two-dimensional cylinder. Measurements of the wake velocity profile of the cylinder were performed using a pitot-static tube. Tabs were mounted on the cylinder. Tab spacing, size and tab angle were varied. Twodimensional drag was computed using the measured velocities and applying the integral momentum theorem. Results show a significant reduction in drag